Strategy to systematize the written comments of the teaching evaluation in the medical residency programs - Carmona Zamudio, Iridian; Hamui Sutton, Liz (Spanish Journal of Medical Education, 2023)
Evaluating the opinions of residents about their programs, campuses, professors and other aspects of their daily work in medical specialties can be useful to improve aspects of their training. The open spaces to obtain written comments (WC) about their experience constitute an opportunity to understand in greater depth the teaching work, the problems in the hospital and the strengths of the educational program. We propose a three-step strategy to systematize the WC exemplified by the analysis of 721 WC obtained through the Teacher Evaluation Instrument, applied virtually in August 2022. WC require careful reading and can be coded to identify categories and from there theorize the findings. In the field of medical residences, we propose the classification into three general categories: structural, organizational and interpersonal for its application in future studies of this nature. The report of the experience and the evaluation of the events are central elements to approach what happens in educational spaces in clinical practice.